The Interoperative - Adriaan Geuze; Matthew Skjonsberg (Oz, 2012)
Infrastructure can be wielded as a means of promoting the common good or as an institutional weapon of exploitation. Regardless of how a particular infrastructure is represented, it is not always clear which role it plays at any given moment.